Development of the Oxford Participation and Activities Questionnaire: constructing an item pool - Kelly L; Jenkinson C; Dummett S; Dawson J; Fitzpatrick R; Morley D (Patient Related Outcome Measures, 2015)
Laura Kelly, Crispin Jenkinson, Sarah Dummett, Jill Dawson, Ray Fitzpatrick, David Morley Health Services Research Unit, Nuffield Department of Population Health, University of Oxford, Oxford, UK Purpose: The Oxford Participation and Activities Questionnaire is a patient-reported outcome measure in development that is grounded on the World Health Organization International Classification of Functioning, Disability, and Health (ICF). The study reported here aimed to inform and generate an item pool for the new measure, which is specifically designed for the assessment of participation and activity in patients experiencing a range of health conditions. Methods: Items were informed through in-depth interviews conducted with 37 participants spanning a range of conditions. Interviews aimed to identify how their condition impacted their ability to participate in meaningful activities. Conditions included arthritis, cancer, chronic back pain, diabetes, motor neuron disease, multiple sclerosis, Parkinson's disease, and spinal cord injury. Transcripts were analyzed using the framework method. Statements relating to ICF themes were recast as questionnaire items and shown for review to an expert panel. Cognitive debrief interviews (n=13) were used to assess items for face and content validity. Results: ICF themes relevant to activities and participation in everyday life were explored, and a total of 222 items formed the initial item pool. This item pool was refined by the research team and 28 generic items were mapped onto all nine chapters of the ICF construct, detailing activity and participation. Cognitive interviewing confirmed the questionnaire instructions, items, and response options were acceptable to participants. Conclusion: Using a clear conceptual basis to inform item generation, 28 items have been identified as suitable to undergo further psychometric testing. A large-scale postal survey will follow in order to refine the instrument further and to assess its psychometric properties. The final instrument is intended for use in clinical trials and interventions targeted at maintaining or improving activity and participation. Keywords: ICF, in-depth interviews, cognitive debrief interviews, questionnaire